DMP 323, a nonpeptide cyclic urea inhibitor of human immunodeficiency virus (HIV) protease, specifically and persistently blocks intracellular processing of HIV gag polyprotein. - Rayner, M M (1994)
DMP 323, a C-2-symmetrical cyclic urea, is representative of a new class of inhibitors of human immunodeficiency virus protease. In this study, we correlate the potent antiviral activity of DMP 323 in acute infections with antiprotease activity assessed by monitoring the inhibition of the processing of viral gag precursor polyprotein from chronically infected lymphoid and monocytoid cell lines. Electron microscopic examination confirmed that the inhibition of gag processing was associated with the production of immature viral particles. Reduction of DMP 323 in the environment of unprocessed gag viral particles did not result in the resumption of gag processing for at least 72 h.